PENGELOLAAN LINGKUNGAN SECARA ISLAMI BERDASARKAN HADITS DAN FIQH: PENGELOLAAN LINGKUNGAN - Afandi; Muhammad Singgih (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2018)
In a physical sense, the word environment is identical to all aspects concerning air, water, soil and plants and their interactions around us. In the Qur'an, there are many verses that mention the environment, even on a very large scale, covering land, sea, mountains, atmosphere, earth, and sky. Unlike the modern scientific approach which is often separated from religion, the scientific approach in Islam is always associated with piety. For example Allah Almighty likens a person who does riya and does not believe in Allah and the last day is like earth on a rock that is poured by heavy rain, and clean the stone (QS 2: 264). The final verse for environmentalists is the accelerated erosion process. Al-Qur'an here describes the worship activities that are wrong (do riya, do not believe in Allah and the end of the day) are identical with events in nature that also harm humans, namely accelerated erosion. Because God's verses include the written (Al Qur'an) and the unwritten (the universe), this paper approaches environmental problems from both sides. The first side is the extent to which the mind-given man is able to read the unwritten verses that exist in nature, and then pour them in a so-called science of the environment, and the other hand how the written verses instruct humans to pay attention and managing the environment. So that this discussion is in-depth and focuses on one topic, then this paper is limited according to the expertise of the author in the field of soil science, specifically soil and water conservation.